Humanizing Strategic HRM: A Systematic Literature Review of Employee-Centric Value Creation In High-Performance Work Systems - Hikmatul Khasanah (Generate Digital Publishing, 2025)
Objective: This study aims to conduct a systematic literature review on the integration of humanization principles into High-Performance Work Systems (HPWS), with a specific focus on employee-centered value creation mechanisms to bridge the “black box” gap in Strategic Human Resource Management. Research Design & Methods: Using the PRISMA framework, a Systematic Literature Review (SLR) was conducted on 45 high-quality articles (2014–2026) sourced from Scopus, Web of Science, and Google Scholar. The analysis combined qualitative thematic synthesis with bibliometric mapping using VOSviewer to identify conceptual evolution and research clusters. Findings: This study identified five main clusters: performance-based practices, psychological mechanisms, humanization perspectives, organizational outcomes, and human capital. The findings indicate a paradigm shift from a performance-centric model (2014–2017) toward a contemporary focus on humanization (2021–2024), where HPWS acts as a “double-edged sword” influencing both work engagement and work intensification. Implications & Recommendations: Organizations must balance job demands and resources (JD-R) to mitigate the dark side of HPWS. HR practitioners are recommended to prioritize “human-centered HRM” by integrating authentic leadership and flexible work policies to translate HPWS practices into positive experiences for employees. Contribution & Value Added: This study contributes to the literature on Strategic Human Resource Management by integrating Social Exchange Theory and the AMO model to explain how psychological empowerment and well-being mediate the relationship between HPWS and performance, and offers a comprehensive framework for employee-centered sustainable value creation.